Adsorption Characteristics of Antibiotic Meropenem on Magnetic CoFe2O4@Au Nanoparticles - Thi Ngoc Mai Pham; Thi Hieu Hoang; Thu Phuong Nguyen; Quang Khanh Nguyen; Bach Pham; Quoc Anh Hoang; Tien Duc Pham; Thi Anh Huong Nguyen; Anh Tuan Le; Duc Thang Pham (Adsorption Science & Technology)
Adsorption characteristics of the antibiotic meropenem on a novel magnetic material synthesized by surface coating cobalt iron oxide (CFO) with gold nanoparticles (AuNPs) were systematically investigated. The AuNPs can enhance material adsorption capacity by having high affinity towards the thioether and amine groups in the meropenem structure. Au coverage on the CFO surface decreased the saturation magnetization from 55.8 emu/g to 48.8 emu/g, still allowing synthesized CFO@Au nanomaterials to be magnetically recoverable. The CFO@Au nanomaterials showed enhanced adsorption capacity of 25.5 mg/g at optimum conditions of pH 4.0 adsorption time 120 min, and adsorbent mass 0.05 g. Adsorption equilibrium was in accordance with a monolayer Langmuir isotherm, while the adsorption kinetics followed pseudo-first-order kinetics and intraparticle diffusion models. This work provides a simple method to prepare a magnetic composite material with high adsorption efficiency for meropenem and probably other thioether-containing substances.